Studies on metal-organic frameworks of Cu(II) with isophthalate linkers for hydrogen storage - Yan, Yong; Yang, Sihai; Blake, Alexander J.; Schröder, Martin (American Chemical Society, 2014)
Hydrogen (H2) is a promising alternative energy carrier due to its environmental benefits, high energy density and its abundance. However, development of a practical storage system to enable the “Hydrogen Economy” remains a huge challenge. Metal-organic frameworks (MOFs) are an important class of crystalline coordination polymers constructed by bridging metal centers with organic linkers, and show promise for H2 storage due to their high surface area and tuneable properties. We summarize our research on novel porous materials with enhanced H2 storage properties, and describe frameworks derived from 3,5-substituted dicarboxylates (isophthalates) that serve as versatile molecular building blocks for the construction of a range of interesting coordination polymers with Cu(II) ions. A series of materials has been synthesised by connecting linear tetracarboxylate linkers to {Cu(II)2} paddlewheel moieties. These (4,4)-connected frameworks adopt the fof-topology in which the Kagomé lattice layers formed by {Cu(II)2} paddlewheels and isophthalates are pillared by the bridging ligands. These materials exhibit high structural stability and permanent porosity, and the pore size, geometry and functionality can be modulated by variation of the organic linker to control the overall H2 adsorption properties. NOTT-103 shows the highest H2 storage capacity of 77.8 mg g−1 at 77 K, 60 bar among the fof-type frameworks. H2 adsorption at low, medium and high pressures correlates with the isosteric heat of adsorption, surface area and pore volume, respectively. Tri-branched C3-symmetric hexacarboxylate ligands with Cu(II) give highly porous (3,24)-connected frameworks incorporating {Cu(II)2} paddlewheels. These ubt-type frameworks comprise three types of polyhedral cage: a cuboctahedron, truncated tetrahedron and a truncated octahedron which are fused in the solid state in the ratio 1:2:1, respectively. Increasing the length of the hexacarboxylate struts directly tunes the porosity of the resultant material from micro- to mesoporosity. These materials show exceptionally high H2 uptakes owing to their high surface area and pore volume. NOTT-112, the first reported member of this family reported, adsorbs 111 mg g−1 of H2 at 77 K , 77 bar. More recently, enhanced H2 adsorption in these ubt-type frameworks has been achieved using combinations of polyphenyl groups linked by alkynes to give an overall gravimetric gas capacity for NU-100 of 164 mg g−1 at 77 K, 70 bar. However, due to its very low density NU-100 shows a lower volumetric capacity of 45.7 g L-1 compared with 55.9 g L-1 for NOTT-112, which adsorbs 2.3 wt% H2 at 1 bar, 77K. This significant adsorption of H2 at low pressures is attributed to the arrangement of the {Cu24(isophthalate)24} cuboctahedral cages within the polyhedral structure. Free metal coordination positions are the first binding sites for D2, and in these ubt-type frameworks there are two types of Cu(II) centres, one with its vacant site pointing into the cuboctahedral cage and another pointing externally. D2 molecules bind first at the former position, and then at the external open metal sites. However, other adsorption sites between the cusp of three phenyl groups and a Type I pore window in the framework are also occupied. Ligand and complex design feature strongly in enhancing and maximising H2 storage, and, although current materials operate at 77 K, research continues to explore routes to high capacity H2 storage materials that can function at higher temperatures.